My first colors (Chicago, USA PI Kids, 2022)
"Spin the wheels to mix colors and explore the rainbow with Baby Einstein friends! Six easy-to-spin wheels encourage curiosity and keep little hands engaged at story time.'"-- Provided by publisher
Scientific Notions
Keywords: Board books; Colors